Eksplorasi Filosofis Pendidikan Akhlak dalam Islam Kajian terhadap Konsep-Konsep Al-Qur'an dan Hadits - Saepul Rohim, Saepul; Helmi; Helmawati (Universitas Majalengka, 2024)
The purpose of this study is to find out the philosophical value of moral education in Islam. This type of research is based on literature and the method of data collection collects various documents from various books, journals, letters in the Qur'an and some Hadith related to the title or research problem. The results of this study include in Q.S At-Tiin: 4, Q.S Luqman: 13-14, Q.S Al-Ahzab: 21 and one of the hadiths of the Prophet Muhammad PBUH narrated and many other hadiths that discuss moral education. The verses and hadiths that have been described above certainly discuss moral education in Islam, starting from explaining the meaning or meaning of moral education and also explaining the implementation of moral education or being taught in terms of its application or practices in daily life to achieve prosperity in this world and the hereafter, of course, by carrying out all the commands of Allah SWT by making the Messenger of Allah as Uswatun Hasanah (a good example) in this life, of course, in highlighting the Morals of the Prophet PBUH as a way for us to achieve the Pleasure of Allah SWT.